2015
DOI: 10.1016/j.neurobiolaging.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of increased calcineurin activity rescues impaired homeostatic synaptic plasticity in presenilin 1 M146V mutant

Abstract: Alzheimer disease (AD) is one of the most common neurodegenerative diseases characterized by memory loss and cognitive impairment. While the majority of AD cases are sporadic, some are caused by mutations in early-onset familial AD (FAD) genes. One FAD gene encodes presenilin 1 (PS1), and a PS1 mutation in methionine 146 impairs homeostatic synaptic plasticity (HSP). We have previously shown that Ca2+ and calcineurin activity are critical regulators of HSP. Here, we confirm that ER-mediated Ca2+ signals are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 58 publications
(126 reference statements)
0
59
0
Order By: Relevance
“…Hippocampal PSD fraction preparation from brain was performed as previously described (Kim et al , 2015). Equal amounts of protein were loaded on 10% SDS-PAGE gels and transferred to nitrocellulose or PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
“…Hippocampal PSD fraction preparation from brain was performed as previously described (Kim et al , 2015). Equal amounts of protein were loaded on 10% SDS-PAGE gels and transferred to nitrocellulose or PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
“…Another study corroborated the deficits in synaptic scaling in hippocampal neurons from Psen1 M146V knock‐in mice, and showed increased calcineurin activity and decreased GluA1 Ser845 phosphorylation in these neurons (Kim et al . ).…”
Section: Homeostatic Synaptic Plasticity and Diseasementioning
confidence: 97%
“…Different lines of evidence indicate that defects in homeostatic plasticity contribute to the pathogenesis of neurological and neuropsychiatric disorders. Alterations in homeostatic signaling have been implicated in intellectual disability and autism spectrum disorders (Soden and Chen 2010;Blackman et al 2012;Qiu et al 2012), schizophrenia (Dickman and Davis 2009), epilepsy (Houweling et al 2005), and in neurodegenerative disorders such as Alzheimer's disease (Pratt et al 2011;Kim et al 2015) and Huntington's disease (Rocher et al 2016). Most of the evidence is related to genes that have been linked to human diseases and that when mutated interfere with homeostatic plasticity [reviewed in (Wondolowski and Dickman 2013)].…”
Section: Homeostatic Synaptic Plasticity and Diseasementioning
confidence: 99%
“…Reports by Kim and colleagues from studies performed in presenilin 1-mutant model of AD provided some mechanistic insights into the cognitive decline improvement resulting from reducing calcineurin activation in affected brains [25, 208]. These authors observed that the inhibition of abnormally increased calcineurin activity characteristic of the disease resulted in the stabilization of the phosphorylation of GluA1, a subunit of Ca 2+ -permeable AMPA receptors, and promoted synaptic trafficking of Ca 2+ -permeable AMPA receptors, as well as the resulting improvement in animal cognition [25]. Such improvement resulted at least partly from the restoration of Ca 2+ -permeable AMPA receptor-mediated hippocampal LTP [208].…”
Section: Controversial Roles In Nervous System Diseasesmentioning
confidence: 99%